2018
DOI: 10.1073/pnas.1713129115
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein oligomers induce early axonal dysfunction in human iPSC-based models of synucleinopathies

Abstract: Significanceα-Synuclein (α-Syn) aggregation underlies neurodegeneration in synucleinopathies. However, the nature of α-Syn aggregates and their toxic mechanisms in human pathology remains elusive. Here, we delineate a role of α-Syn oligomeric aggregates for axonal integrity in human neuronal models of synucleinopathies. α-Syn oligomers disrupt anterograde axonal transport of mitochondria by causing subcellular changes in transport-regulating proteins and energy deficits. An increase of α-Syn oligomers in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
205
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(218 citation statements)
references
References 43 publications
(60 reference statements)
12
205
1
Order By: Relevance
“…α-synuclein can also bind mitochondria-associated ER membranes (MAM) (Guardia-Laguarta et al, 2014), and evidence indicating that its absence impairs mitochondria lipid composition, function, fusion, and trafficking (Ellis et al, 2005;Faustini et al, 2019) supports that the protein can play a physiological role in the regulation of mitochondrial homeostasis. This hypothesis is in line with findings showing that pathological α-syn aggregates or oligomers produce mitochondria fragmentation, impair mitochondrial trafficking, and lead to respiration failure (Devi et al, 2008;Nakamura et al, 2011;Tapias et al, 2017;Prots et al, 2018;Wang et al, 2019).…”
Section: α-Synuclein: Physiological Function and Role In Pdsupporting
confidence: 91%
“…α-synuclein can also bind mitochondria-associated ER membranes (MAM) (Guardia-Laguarta et al, 2014), and evidence indicating that its absence impairs mitochondria lipid composition, function, fusion, and trafficking (Ellis et al, 2005;Faustini et al, 2019) supports that the protein can play a physiological role in the regulation of mitochondrial homeostasis. This hypothesis is in line with findings showing that pathological α-syn aggregates or oligomers produce mitochondria fragmentation, impair mitochondrial trafficking, and lead to respiration failure (Devi et al, 2008;Nakamura et al, 2011;Tapias et al, 2017;Prots et al, 2018;Wang et al, 2019).…”
Section: α-Synuclein: Physiological Function and Role In Pdsupporting
confidence: 91%
“…The reduction in anterograde mitochondrial transport has recently been specifically associated with the accumulation of oligomeric species in neuronal iPSC isolated from an individual with SNCA duplication (Prots et al . ).…”
Section: Cellular Models Of α‐Syn Pathologymentioning
confidence: 97%
“…Such changes in synaptic integrity are likely early occurring pathological events, as the accumulation of oligomers following α‐Syn over‐expression in human iPSC derived neurons was recently reported to coincide with numerous synaptic structural abnormities alongside a general loss of pre‐synaptic protein expression and axonal fibers (Prots et al . ). Interestingly, high levels of α‐Syn may not only affect neuronal communication via synaptic dysfunction but also via reducing the gap junction intercellular communications (Sung et al .…”
Section: Cellular Models Of α‐Syn Pathologymentioning
confidence: 97%
See 1 more Smart Citation
“…The clinical phenotype of E46K patient features rapid and severe disease progression with early onset of the parkinsonism of DLB 11 . Previous studies have shown that the E46K mutation can enhance α -syn fibril formation and α -syn pathology in vitro and in cultured cells 13,17,18 . Solid state NMR study has shown that the E46K mutation causes large conformational changes of the fibril structure 19 .…”
Section: Introductionmentioning
confidence: 97%